P3.211 Extremely High Risk of Syphilis Co-Infection and Re-Diagnosis Among Men Who Have Sex with Men Living with HIV in Ontario, Canada. (13th July 2013) - Burchell, A N; Allen, V; Moravan, V; Gardner, S; Raboud, J; Tan, D; Bayoumi, A; Kaul, R; Remis, R S; Rourke, S B
Abstract : Background: Since 2000, new syphilis cases increased ten-fold in Canada, particularly among men who have sex with men (MSM) co-infected with HIV. We calculated the prevalence and incidence of syphilis in a large cohort of HIV-positive MSM. Methods: We analysed data from 2, 903 MSM followed from 2000 to 2009 in the OHTN Cohort Study, an ongoing cohort of persons in HIV care in Ontario, Canada. Syphilis serology was obtained via record linkage with the provincial public health laboratories. We classified reactive rapid plasma reagin results as acute (≥ 16:1) or non-acute (≤ 8:1) and calculated the lifetime and annual prevalence of syphilis and incidence of new syphilis diagnoses and re-diagnoses. Risk factors were identified using Poisson regressions and are reported as rate ratios (RR) with 95% confidence intervals (CI). Results: We linked 7, 036 syphilis results from 2, 422 men (83.4%). Lifetime prevalence was 23.4% (95% CI 21.7, 25.2) by 2009. The annual prevalence of acute syphilis increased from 0.1% (95% CI 0.002, 0.5) in 2000 to 3.8% (95% CI 3.0, 4.6) in 2009. Among 1505 men with a negative specimen, incidence of first syphilis infection was 2.7/100PY (95% CI 2.3, 3.1), with higher rates in men who were aged < 30 years (RR = 2.8, 95% CI 1.4–5.5), ART-naïve (RR = 1.7, 95% CI 1.2–2.5), and had high viral load (> 100, 000 copies/mL cf undetectable: RR = 1.8, 95% CI 1.1–3.0). Incidence rose over time, peaking in 2009 at 3.97/100PY (95% CI 3.0, 5.2). Among 591 men with past infection, the rate of re-diagnosis was 4.8 per 100PY (95% CI 3.7, 5.5), with 35% experiencing multiple re-diagnoses. Conclusion: Syphilis incidence among HIV-positive MSM was over 300 times greater than in the general male population. Temporal and regional trends mimicked provincial surveillance reports and remain extremely high despite public health education and testing campaigns. Re-diagnosis was common, suggesting treatment failure or re-infection. Novel syphilis control efforts are urgently needed.